Paul Rosenstein-Rodan and the birth of development economics - Michele Alacevich (Duke University, Center for the History of Political Economy (CHOPE), 2020)
This paper, based on previously untapped archival sources, offers an assessment of the life and thought of Paul Rosenstein-Rodan, a pioneer of development economics and one of the first articulators of both the "Big Push" and "balanced growth" theories. In addition to documenting the early life of Rosenstein-Rodan, this paper discusses two critical junctures in the history of development economics, namely, the birth of the discipline in the late 1940s, and its decline approximately a quarter century later. Rosenstein-Rodan was a fundamental player in both instances. Through the lens of his experiences it is possible to understand the eclectic beginnings of development economics and locate some of its most important roots in the intellectual milieu of inter-war Europe, from Vienna to London via Eastern and Southern Europe. What's more, Rosenstein-Rodan's subsequent career epitomizes the arc of development economics, casting new light on the debates and practices that shaped the discipline during its rise, and on the unresolved issues that help explain its decline.
Keywords: 330